Casablanca - Alison, Joan.; Bergman, Ingrid, 1915-1982.; Bogart, Humphrey, 1899-1957.; Burnett, Murray; Curtiz, Michael, 1888-1962.; Edeson, Arthur, 1891-1970.; Epstein, Julius J., 1909-2000.; Epstein, Philip G.; Greenstreet, Sydney; Henreid, Paul.; Koch, Howard; Lorre, Peter; et al. ([Burbank, Calif.] : Warner Home Video, 2003)
Set in World War II Morocco within a city filled with European refugees. A bitter nightclub owner helps his former lover and her Resistance-hero husband escape from the Nazis.
"A production of WNET/New York in association with Turner Entertainment Co."
From a play by Murray Burnett, Joan Alison.
Publicado como película en 1942.
Music by Max Steiner ; director of photography, Arthur Edeson ; ; film editor, Owen Marks ; executive producer, Jack Warner.
Humphrey Bogart, Ingrid Bergman, Paul Henreid, Claude Rains, Conrad Veidt, Sydney Greenstreet, and Peter Lorre.
MPAA rating: PG.
Keywords: Guerra mundial II, 1939-1945 -- Refugiados; Guerra mundial II, 1939-1945. -- Actividades clandestinas; Marruecos -- Historia; Movimiento de paz; Películas cinematográficas